การสังเคราะห์โดยใช้ไมโครเวฟและการวิเคราะห์ลักษณะเฉพาะของไทเทเนียมไดออกไซด์ระดับนาโนเมตร - นุชนาพร พิจารณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
Nano -scaled titanium dioxide (TiO₂) was synthesized by a microwave-assisted process using alkali and microwave irradiation heat mediated hydrolysis of titaniumoxysulfate as the starting material. The coexistence of three polymorphs of TiO₂ (anatase, brookite and rutile) was found. The properties of the TiO₂ depending on, (i) synthesis pH, (ii) microwave power, (iii) irradiation time, (iv) aging time after irradiation for precipitation, and (v) calcination temperature. The obtained TiO₂ powders were characterized for their mineral phase by X-ray diffraction, using Scherrer’s equation and Rietveld analysis to quantify the crystallite size and phase composition, respectively. The results showed a significant difference in terms of the phase composition and estimated crystallite size of the TiO₂ prepared under different conditions, and so it is possible to select the optimal synthesis condition for the desired mineral phase. The morphologies of TiO₂ powders were observed by a scanning electron microscope (SEM). The results showed agglomerates in various sizes. Particle size distribution and surface charge of the TiO₂ were studied by Zetasizer. The results showed nono-scaled TiO₂ with a good distribution of highly negatively charged particles. The photocatalytic activities of the obtained TiO₂ powders were evaluated through the decomposition of methylene blue in comparison with P25 (Degussa). Results showed that the TiO₂ prepared at conditions of pH 10, 100 watt microwave power, irradiation time of 10 min, aging for precipitation 42 h was most effective when compared with others and P25